Spain : Vulnerabilities of Private Sector Balance Sheets and Risks to the Financial Sector Technical Notes. (IMF Staff Country Reports; Country Report ;, 2012)
This technical note assesses the vulnerabilities of household and corporate sector balance sheets and quantifies the potential impacts from macroeconomic shocks using sensitivity and contingent claims analyses. The note analyzes the risks to the Spanish financial stability arising from household indebtedness. The analysis expands the use of microlevel data to assess household vulnerabilities, distinguishing between indebted and nonindebted households as well as accounting for the allocation of debt, debt service burden, and households' income and assets.